Successful management of perivascular epithelioid cell tumor of the rectum with recurrent liver metastases: A case report. Issue 31 (August 2018) - Lin, Kung-Hung; Chang, Nai-Jen; Liou, Li-Ren; Su, Ming-Shan; Tsao, Min-Jen; Huang, Meng-Lin
Abstract: Rationale: The perivascular epithelioid cell tumor (PEComa) is rare in young man and rarely occurs in the large intestine. Patient concerns: The clinical characteristics, diagnosis, and managements in a 28-year-old boy who presented with sudden onset of cramping and abdominal pain and intermittent melena with a blood pressure of 74/39 mm Hg was retrospectively reviewed. CT scan of the abdomen revealed a 8.9 × 7.2 cm mass in the pelvic floor. Diagnoses: Given the difficulty of obtaining a diagnostic specimen, surgical resection was performed. The pathology report of lower anterior resection was malignant PEComa of the rectum in 2006. Interventions: Treatment consisted of surgical resection only without additional adjuvant therapy. Over the next 49 months (until 2010) after surgery, abdominal CT showed a 0.6-cm hypodense mass over the liver with suspected liver metastasis. He refused any further evaluation and treatment. After 4 years (2014), abdominal CT showed that the original mass had increased from 0.6 to 1.5 cm and the number of tumors had increased from 1 to 3. In August 2014, he underwent a metastatic hepatectomy without additional chemotherapy or radiotherapy. Outcomes: We noted that the metastatic progression was slow in the 4 years after the first operation. At 28 months after metastatic hepatectomy, the patient was doing well. There was also no recurrence of the PEComa of the rectum at the 120-month follow-up in 2016. Lessons: To the best of our knowledge, this is the first report of a PEComa of the rectum with liver metastases treated with only surgical resection. At approximately 8.8 cm, this is the largest PEComa of the rectum reported in the recent literature.